Effect of Reaction Temperature on the Characterizations of Cobalt Ferrite Nanoparticles (International Journal of Scientific Research in Science and Technology, 2024)
This study investigates the structural and magnetic properties of CoFe2O4 nanoparticles synthesized by the co-precipitation method at various reaction temperatures. X-ray diffraction (XRD) analysis confirms that the nanoparticles maintain a cubic spinel structure, with characteristic peaks stable across the 30 - 90°C temperature range, indicating that these temperatures do not affect the crystal structure. However, increasing the temperature results in larger particle sizes, higher saturation magnetization, and increased coercivity. The precipitate consistently exhibits characteristic soft magnetic properties, with no significant transitions in size or structure leading to drastic changes in magnetic behavior. These findings provide valuable insights for optimizing the synthesis process to control the structural and magnetic properties of CoFe2O4 nanoparticles, making them suitable for various practical applications.